2012
DOI: 10.1002/jnr.23111
|View full text |Cite
|
Sign up to set email alerts
|

Altered balance between excitatory and inhibitory inputs onto CA1 pyramidal neurons from SV2A‐deficient but not SV2B‐deficient mice

Abstract: Synaptic vesicle protein 2 (SV2) is a glycoprotein that exists in three isoforms, SV2A, SV2B, and SV2C. SV2A knockout (KO) mice and SV2A/SV2B double KO (DKO) mice, but not SV2B KO animals, start to experience severe seizures and weight loss 7 days after birth and die at about postnatal day (P)14-P23. Because excitatory and inhibitory inputs play a major role in controlling neuronal excitability in the hippocampus, we examined the effects of SV2A and/or SV2B deletions on glutamatergic and GABA(A) neurotransmiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 48 publications
(71 reference statements)
1
31
0
Order By: Relevance
“…S3 C and D ) nor the amplitude of mEPSCs (Fig. S3 C and E ) was altered in slices from TKO mice, akin to what has been observed at hippocampal synapses from SV2A single KOs or SV2A/B DKOs (29) but distinct from Syt1 null mice (30). …”
Section: Resultsmentioning
confidence: 54%
“…S3 C and D ) nor the amplitude of mEPSCs (Fig. S3 C and E ) was altered in slices from TKO mice, akin to what has been observed at hippocampal synapses from SV2A single KOs or SV2A/B DKOs (29) but distinct from Syt1 null mice (30). …”
Section: Resultsmentioning
confidence: 54%
“…Inhibition of SV2A activity might therefore be expected to affect both glutamatergic and GABAergic synaptic transmission. Moreover, deletion of the SV2A gene has been shown to manifest opposite effects on glutamatergic and GABAergic neurotransmission, with decreased GABAergic synaptic currents [20] but increased glutamatergic transmission [21]. Thus, LEV might be acting as a positive allosteric modulator of SV2A, resulting in decreased glutamate release.…”
Section: Discussionmentioning
confidence: 99%
“…However, SV2A-KO mouse studies have demonstrated that SV2A deletion results also in the reduced action potential-dependent release of the inhibitory neurotransmitter GABA in this hippocampal region. This imbalance between excitatory and inhibitory neurotransmission in the hippocampus could be responsible for seizures, at least concerning those observed in SV2A-KO mice [10, 12]. The possibility thus exists that GriK4:SV2A-cKO does not affect the neuronal population responsible for epilepsy, as the GABAergic system is preserved.…”
Section: Discussionmentioning
confidence: 99%
“…However, miniature inhibitory postsynaptic current (mIPSC) appeared unchanged, meaning that the protein machinery allowing the vesicles filled with GABA is not affected but the coupling molecular machinery between the action potential reaching the synaptic button and the GABAergic-dependent neurotransmission is. [10, 12]. …”
Section: Introductionmentioning
confidence: 99%